Census and the construction of communalism in India - Bhagat, R.B. (2001)
The article highlights the role of the census in the construction of mutually exclusive religious communities and their particular demographic and geographical features in furthering the communal consciousness in colonial India through the policy of divide and rule. The perpetuation of demographic religions continued in independent India's categorisation census exercises where the demographic anxieties are paramount and the planks of social justice ignored. - Reproduced
Keywords: Communalism - India; India - Population; Population censuses